2017
DOI: 10.3390/ijerph14050513
|View full text |Cite
|
Sign up to set email alerts
|

Hydration, Fluid Intake, and Related Urine Biomarkers among Male College Students in Cangzhou, China: A Cross-Sectional Study—Applications for Assessing Fluid Intake and Adequate Water Intake

Abstract: The objectives of this study were to assess the associations between fluid intake and urine biomarkers and to determine daily total fluid intake for assessing hydration status for male college students. A total of 68 male college students aged 18–25 years recruited from Cangzhou, China completed a 7-day cross-sectional study. From day 1 to day 7; all subjects were asked to complete a self-administered 7-day 24-h fluid intake record. The foods eaten by subjects were weighed and 24-h urine was collected for thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
72
5
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(100 citation statements)
references
References 35 publications
14
72
5
1
Order By: Relevance
“…For adults, the TFI in current survey differed by only approximately 100 mL/day compared with the fluid intake survey of adults in four Chinese cities (1584 vs 1488, mL/day) in 2010 [20]. In a survey with the Liq.In 7 record specifically conducted in young adults (aged 18–25 years) in China in 2015, TFI was 1342 mL/day and less than the adults in this survey [37]. In a systematic review including 273 studies in different countries (only one Asia survey in China was included; the majority being USA and European surveys), it was concluded that TFI varied between 0.6 and 3.5 mL/day in the general population and 0.6–1.8 mL/day amongst children, 0.8–2.0 mL/day amongst adolescents, and 0.8–3.4 mL/day amongst adults [38].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…For adults, the TFI in current survey differed by only approximately 100 mL/day compared with the fluid intake survey of adults in four Chinese cities (1584 vs 1488, mL/day) in 2010 [20]. In a survey with the Liq.In 7 record specifically conducted in young adults (aged 18–25 years) in China in 2015, TFI was 1342 mL/day and less than the adults in this survey [37]. In a systematic review including 273 studies in different countries (only one Asia survey in China was included; the majority being USA and European surveys), it was concluded that TFI varied between 0.6 and 3.5 mL/day in the general population and 0.6–1.8 mL/day amongst children, 0.8–2.0 mL/day amongst adolescents, and 0.8–3.4 mL/day amongst adults [38].…”
Section: Discussionmentioning
confidence: 96%
“…In a systematic review including 273 studies in different countries (only one Asia survey in China was included; the majority being USA and European surveys), it was concluded that TFI varied between 0.6 and 3.5 mL/day in the general population and 0.6–1.8 mL/day amongst children, 0.8–2.0 mL/day amongst adolescents, and 0.8–3.4 mL/day amongst adults [38]. Another survey using the Liq.In 7 record in 2015 also indicated that only approximately a quarter of the Chinese young adults met the recommendation [37]. Harmonized cross-sectional fluid specific surveys performed in 15 countries showed that a relatively high proportion of subjects (38%) failed to meet the recommendation on fluid intake and this proportion significantly varied among countries [39].…”
Section: Discussionmentioning
confidence: 99%
“…While among elderly aged ≥60 years from NHANES 2011-2014, 29.6% and 33.3% of women and men had Sosm (osmolality of serum) levels indicative of impending dehydration, with 10.2% and 12.6% of women and men had Sosm levels indicative of dehydration [20]. In China, there was merely one study exploring hydration status among male young adults, which showed that only 35.3% of them were in optimal hydration status [21]. Research showed that the participants with low total drinking fluids excreted significantly less volume of urine than those with high total drinking fluids over each 24 h period [22].…”
Section: Introductionmentioning
confidence: 99%
“…Because the GRHI took place over a single 24 h period, it is possible that a second day of increased water intake within many of the intervention groups may have allowed those participants to return to U col < 4. Although from a different geographical population, the finding that free-living individuals with habitual TWI > 2500 mL day −1 were associated with optimal hydration [39] supports the theory that a longer duration of G +1.50 or G +2.25 GRHI would have been successful in returning a greater proportion to more desirable urine concentrations.…”
Section: Discussionmentioning
confidence: 58%